1999
DOI: 10.1002/(sici)1097-4628(19990815)73:7<1259::aid-app20>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultraviolet radiation on photodegradation of collagen

Abstract: Photodegradation of solvent-cast collagen type I films and photostabilization of collagen by vitamin E were studied. These films were exposed to polychromatic radiation from a medium-pressure mercury lamp or monochromatic radiation from the Okazaki Large Spectrograph (OLS). Changes in the molecular structure of collagen were followed by UV-visible and FTIR spectroscopic measurements. Electron spin resonance (ESR) spectroscopic measurements were also carried out to identify the reaction intermediates of photode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…In PVA the action of UV-irradiation causes mainly degradation [18], whereas in collagen it causes mainly conformational transformation (helix-coil transition) [19][20][21].…”
Section: Specimenmentioning
confidence: 99%
“…In PVA the action of UV-irradiation causes mainly degradation [18], whereas in collagen it causes mainly conformational transformation (helix-coil transition) [19][20][21].…”
Section: Specimenmentioning
confidence: 99%
“…It has been reported that the process of UV irradiation can induce crosslinks into collagen fibrils. However, this is complicated by peptide bond scission events that may also occur through free radical mechanisms [12][13][14][15][16]. The photochemical reactions may be attributed to direct absorption by tyrosine/phenylalanine or to peptide bonds [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that purified collagen, in the form of powder or solution, may increase insoluble fraction by additive or photo-crosslinking reactions. It is also supported that degradation of collagen results from denaturation of triple helix structure, which also provokes the decay of collagen's bioactivity [15,17,21]. The structural damage of collagen has been widely re ported as turning phenylalanine into tyrosine (struc tural scission of-OH) [17,22], decarboxylation (struc tural scission of-C=0) [17,22,23], hydrogen abstrac tion (structural scission of-N-H) [17,23,24], thermal denaturation [18,[25][26], and general oxidative degra dation [ 17,18,[23][24][25].…”
Section: Biomedical Engineering-applications Basis and Communications 21mentioning
confidence: 95%
“…Collagen has a supercoiled triple helix conforma tion and is sensible to different degrees of radiation [15][16][17][18][19][20]. It is reported that purified collagen, in the form of powder or solution, may increase insoluble fraction by additive or photo-crosslinking reactions.…”
Section: Biomedical Engineering-applications Basis and Communications 21mentioning
confidence: 99%